2020
DOI: 10.1080/13876988.2020.1773263
|View full text |Cite
|
Sign up to set email alerts
|

Policy Effectiveness through Configurational and Mechanistic Lenses: Lessons for Concept Development

Abstract: The aim of this article is to build up a concept-informed research design to answer "why and how" a policy can make a difference. It demonstrates the potential and challenges of an innovative multimethod approach, which combines a configurational and mechanistic view to policy effectiveness. The article hereto draws on experiences in applying Qualitative Comparative Analysis and Process Tracing in one single evaluation. The study calls for a rigorous treatment of concepts, especially to avoid the risk of mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…We thus conceive it as a passive contextual condition, rather than a causal one. In QCA this distinction is seldom made, with the exception of the two-step QCA variant in which one distinguishes remote and proximate conditions (but various approaches to the conceptualization of remote and proximate exist) (Schneider and Wagemann, 2006;Schneider 2019), and some recent contributions on QCA-PT multimethod designs (see Pattyn et al 2020).…”
Section: Omitted Contextual Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus conceive it as a passive contextual condition, rather than a causal one. In QCA this distinction is seldom made, with the exception of the two-step QCA variant in which one distinguishes remote and proximate conditions (but various approaches to the conceptualization of remote and proximate exist) (Schneider and Wagemann, 2006;Schneider 2019), and some recent contributions on QCA-PT multimethod designs (see Pattyn et al 2020).…”
Section: Omitted Contextual Conditionsmentioning
confidence: 99%
“…Earlier research had shown that plenty of employees fail to adequately transfer the skills that they had learned in the training to the work environment. Therefore, combining QCA with methods to probe mechanistic causation enabled us to uncover under which combination of conditions (QCA) a training programme would lead to successful training transfer, and how (PT) this happened or 'what worked' in the successful cases (see Pattyn et al 2020;Álamos-Concha et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…While the alignment mechanism is about the process of fitting together the social and the technical dimensions, the context is about the combination of crucial causal conditions that jointly and synergistically produce the outcome of interest (El Sawy et al, 2010). Put differently, the alignment mechanism explains the "how" of causation whereas the complex combination of causal conditions (i.e., the context) explains the "why" of causation (Pattyn et al, 2020;Wynn & Williams, 2020). Hence, the generative view points to a relationship between causal mechanisms and their effects which is not fixed but contingent, that is, dependent upon a specific combination of causal conditions (or context).…”
Section: Discussionmentioning
confidence: 99%
“…Few would argue that mechanistic causation can be directly uncovered with QCA, which applies analytical procedures to establish differences between types of cases. However, the presence of a causal mechanism can be found with process-tracing (PT) methods (Beach and Pedersen 2019;Pattyn et al 2020). Under a mechanistic theory of causation, QCA cannot be used to establish causal relations, but it can be used instrumentally to "find potential causes, select appropriate cases for within-case analysis, and enable cautious generalizations about processes to small, bounded sets of cases" (Beach and Kaas 2020, 9).…”
Section: Mechanistic Theoriesmentioning
confidence: 99%